Development of numerical step-by-step method for calculating boundary layers - Mai, Vu Ba (Vietnam Journal of Mechanics, 1993)
In this paper was proposed a development of numerical step-by-step method for calculating boundary layers. As an example showed all the coefficients an0 of initial velocity’s profile had been calculated by experiment.